The Effectiveness of Assertive Training Techniques in Group Counseling Services for Reducing Verbally Aggressive Behavior Among Junior High School Students - Aura Meutia Pangesti; Dimas Ardika Miftah Farid (Mitra Ash-Shibyan: Jurnal Pendidikan dan Konseling, 2026)
This study examined the preliminary effectiveness of Assertive Training implemented through group counseling in reducing verbal aggressive behavior among junior high school students. A quantitative one-group pretest–posttest design was employed involving six students identified as exhibiting verbal aggressive behavior. Data were collected using a verbal aggressive behavior scale developed from the theoretical frameworks of Berkowitz, Infante and Wigley, and Buss and Perry, covering four dimensions: verbal abuse, sarcasm, slander, and anger. Data were analyzed using the Wilcoxon Signed-Rank Test. The findings showed a statistically significant reduction in verbal aggressive behavior following the intervention (Asymp. Sig. [2-tailed] = 0.028, p < .05). These results provide preliminary empirical evidence that Assertive Training implemented through group counseling may effectively reduce students’ verbal aggressive behavior while promoting more adaptive communication patterns. However, because the study involved a small sample and lacked a control group, the findings should be interpreted cautiously. Further studies employing larger samples and more rigorous experimental designs are recommended to confirm the effectiveness of the intervention. Overall, this study offers preliminary empirical support for the application of Assertive Training as a school-based counseling intervention to reduce verbal aggressive behavior among junior high school students.